Constructive General Neron Desingularization for one dimensional local rings. (May 2017) - Pfister, Gerhard; Popescu, Dorin
Abstract: An algorithmic proof of General Neron Desingularization is given here for one dimensional local rings and it is implemented in Singular . Also a theorem recalling Greenberg' strong approximation theorem is presented for one dimensional local rings.